EDUKASI MENGENAI DAMPAK PERUBAHAN IKLIM TERHADAP LINGKUNGAN LAUT BAGI KELOMPOK PELAJAR SAKA KALPATARU, PRAMUKA, KABUPATEN SUMBAWA - Baiq Hilda Astriana; Aryan Perdana Putra; Muhammad Junaidi (Universitas Mataram, 2023)
Climate change has long developed into a global issue. Even so, most of the focus of this issue still rests on the impact of climate change on the atmosphere and living things that occupy the land on this earth. In addition, despite the incessant campaigns to prevent the worsening of this phenomenon, not all of them are accompanied by concrete actions to reduce the factors that cause climate change. One of the efforts that can be made to encourage public awareness and willingness to contribute to preventing the effects of climate change is to provide education for the younger generation, for example student groups. Therefore, the purpose of this community service activity is to open insight of student groups regarding climate change and its impact on the sea, as well as to provide knowledge about steps taken to prevent climate change from getting worse. The method used in this activity is the provision of material that is relevant to the purpose of the activity. The participants selected were a student group of 50 people who were the members of the Saka Kalpataru, Scouts, Sumbawa Regency. The activity was carried out together with the Scout camp activities in Rhee District, Sumbawa Regency. As a form of evaluation of participants' understanding about the information presented, all participants were asked to fill out an assessment instrument. The result of this evaluation indicates that there has been an increase in participants' knowledge and understanding about the impacts of ocean climate change on marine environment both locally and globally.